Traditional health practitioners' understanding of spirit possession in Gauteng province, South Africa - Ellen M. Thobakgale; Roinah Ngunyulu; Mavis Mulaudzi (AOSIS, 2024)
Background: Traditional health practitioners (THPs) understand spirit possession as a cultural or religious spirit occupying a person, while the mental healthcare providers understand it as a mental illness. The different understanding is based on manifestations that mimic that of mental illness, such as seeing and hearing things that others cannot see or hear. Spirit possession holds different meanings in different cultures and religions that could be either beneficial or detrimental. Furthermore, spirit possession is understood as a channel of communication between the living and the dead or God or a supernatural phenomenon in which a spirit owns a person. Aim: This study explored and interpreted THPs' understanding of spirit possession in Gauteng province, South Africa. Method: Hermeneutic phenomenology study explored and interpreted the THPs' understanding of spirit possession in Gauteng province. In-depth individual interviews were conducted with 12 THPs who were selected through snowball sampling techniques. Data analysis followed Heidegger's and Gadamer's philosophies and Van Manen's six steps of the analytic approach. Results: The findings revealed that THPs understood spirit possession as spiritual illness, ancestral calling and demonic spirit or witchcraft. Conclusion: Traditional health practitioners' understanding of spirit possession could promote mental health and prevent mental illness by providing support to a spirit-possessed person and referral to mental healthcare services. Contribution: This study contributed that not all manifestations presented by persons with spirit possession are actual and clear-cut mental illness, but could be unwritten cultural and/ or religious illnesses that needs cultural and religious services also.